Interaction between body mass index and blood pressure on the risk of vascular stiffness : A community-based cross-sectional study and implications for nursing - Yiyan Wang; Hao Wang; Jie Zhou; Jiaqi Wang; Hengjing Wu; Jing Wu (Elsevier, 2023)
Objective: This study aimed to analyze associations between body mass index (BMI) and vascular measurements (brachial ankle pulse wave velocity [baPWV] and ankle-brachial index [ABI]), whether blood pressure (BP) was involved in the relationship, and implications for nursing. Methods: A cross-sectional study was conducted, including 1,894 middle-aged and older adults who underwent routine health screening at a community medical center in the Zhangjiang community in Shanghai, China. Participants were divided into three groups based on BMI: normal weight (n = 1,202), overweight (n = 480), and obese (n = 212). Multivariate linear regression models and smooth curve fittings were used to evaluate the associations between BMI and indices of vascular stiffness. Mediation analysis examined whether blood pressure mediate the association between BMI and vascular stiffness. Results: Multiple linear regression analysis showed that BMI to be significantly and negatively associated with baPWV (β = −0.06 [−0.10, −0.03]) and ABI (β = −0.004 [−0.005, −0.003]), respectively. The interaction test results of systolic blood pressure (SBP) in the relationship between BMI and baPWV were significant (P for interaction = 0.01). After adjusting for age and sex, mediation analyses showed that BMI and baPWV were correlated (β = 0.090, P < 0.001) and mediated by SBP (β = 0.533, P < 0.001) and diastolic blood pressure (DBP) (β = 0.338, P < 0.001). A negative association was found between BMI and ABI (β = −0.135, P < 0.001), which appeared to be partially mediated by SBP (β = 0.124, P < 0.001) and DBP (β = 0.053, P < 0.001). Additional subgroup analysis based on blood pressure levels did not revealed statistically significant mediating effects. Conclusions: Our findings showed conflicting associations between BMI and non-invasive vascular measurements of arterial stiffness. BP may have a biological interaction in the relationship between BMI and baPWV. Managing blood pressure and weight through comprehensive clinical care is crucial for preventing stiffness or blockage of vessels in middle-aged and older adults.